The concept of capacity in Australian mental health law reform: Going in the wrong direction?. (May 2015) - McSherry, Bernadette; Wilson, Kay
Abstract: The six Australian states and two territories each have legislation that enables the involuntary detention and treatment of individuals diagnosed with mental illness who are considered in need of treatment and where there is evidence of a risk of harm to self or others. A number of governments have undertaken or are currently undertaking reviews of mental health laws in light of the Australian Government's ratification of the Convention on the Rights of Persons with Disabilities. While United Nations bodies have made it clear that laws which enable the detention of and substituted decision-making for persons with disabilities should be abolished, debates in Australia about the reform of mental health legislation have largely focused on Article 12 of the CRPD and what is meant by the right of persons with disabilities to enjoy legal capacity on an equal basis with others. It is argued that a more holistic view of the CRPD rather than the current narrow focus on Article 12 would best serve the needs of persons with mental impairments.